Wind tunnel and numerical data on the ventilation performance of windcatcher with wing wall - Payam Nejat; John Kaiser Calautit; Muhd Zaimi Abd. Majid; Ben Richard Hughes; Iman Zeynali; Fatemeh Jomehzadeh (Data in Brief, 2016)
The data presented in this article were the basis for the study reported in the research articles entitled “Evaluation of a two-sided windcatcher integrated with wing wall (as a new design) and comparison with a conventional windcatcher” (P. Nejat, J.K. Calautit, M.Z.A. Majid, B.R. Hughes, I. Zeynali, F. Jomehzadeh, 2016) [1] which presents the effect of wing wall on the air flow distribution under using the windcatchers as a natural ventilation equipment. Here, we detail the wind tunnel testing and numerical set-up used for obtaining the data on ventilation rates and indoor airflow distribution inside a test room with a two-sided windcatcher and wing wall. Three models were integrated with wing wall angled at 30°, 45° and 60° and another windcatcher was a conventional two-sided device. The computer-aided design (CAD) three-dimensional geometries which were produced using Solid Edge modeler are also included in the data article.